2017
DOI: 10.5007/2175-7925.2017v30n1p37
|View full text |Cite
|
Sign up to set email alerts
|

Métodos de inoculação de Colletotrichum lindemuthianum em sementes de feijão e danos em plântulas

Abstract: ResumoA antracnose causada pelo fungo Colletotrichum lindemuthianum (Sacc. & Magnus) Scrib. é uma das doenças mais sérias da cultura do feijão. Técnicas de inoculação são importantes para avaliações de resistência de genótipos e de métodos de controle em fases iniciais do desenvolvimento de plântulas. Diante da necessidade de se obter plântulas infectadas, o presente trabalho teve por objetivo testar diferentes métodos de inoculação de C. lindemuthianum em sementes de feijão e veriicar o impacto na emergência … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In this study, we opted for 12 hours of exposure to the pathogen, which resulted in a colonization rate of 50% of the seeds, allowing the evaluation of germination and vigor. This behavior corroborates what has already been observed for Colletotrichum lindemuthianum vs. beans (Migliorini et al, 2017) and also for S. sclerotiorum vs. beans, in which there was a reduction of over 60% in seedling emergence in infected seeds (Venturoso et al, 2015).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we opted for 12 hours of exposure to the pathogen, which resulted in a colonization rate of 50% of the seeds, allowing the evaluation of germination and vigor. This behavior corroborates what has already been observed for Colletotrichum lindemuthianum vs. beans (Migliorini et al, 2017) and also for S. sclerotiorum vs. beans, in which there was a reduction of over 60% in seedling emergence in infected seeds (Venturoso et al, 2015).…”
Section: Resultssupporting
confidence: 91%
“…Field emergence: four replications with 50 seeds were used, and emergence evaluation was performed at 30 days after sowing (DAS), accounting for the number of emerged plants, that is, plants that had fully expanded primary leaflets (Migliorini et al, 2017). At 30 DAS the plants present in each plot were collected to quantify plant fresh and dry mass (g).…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…Mota et al (2019) observed 59% to 70% of anthracnose incidence on lima bean stems and leaves in seeds inoculated by direct contact with mycelium and the mannitol water restrictor 14 DAS. Migliorini et al (2017) found 33% and 60% of disease symptoms in bean hypocotyl from seeds inoculated with C. lindemuthianum by immersion in conidia suspension and direct contact with mycelium. Necrotic lesions appeared along the veins in the lower part of leaves, and incidence varied from 88% to 89% among inoculation methods, differing only from the control with 11% incidence on leaves.…”
Section: Discussionmentioning
confidence: 98%